Journalism's crisis of hegemony - Nerone, John C. (Javnost (Ljubljana), 2015)
Although usually considered a longstanding tradition, journalism is a relatively recent assemblage of standards and values governing the news environment. This article discusses the formation of journalism as an ism in the context of the industrialisation of the news media. It situates journalism as an ideology of expert observation within struggles over the power of news media in the first half of the twentieth century. Noting that the ability of journalism to discipline the news depended on bottlenecks in the media system, the article traces the crisis of hegemony that has accompanied the digital transformation of media infrastructure. It concludes by imagining a new hegemonic journalism.
Keywords: Hegemony; History; Journalism; Mass media; Množični mediji; Nadvlada; Novinarstvo; Zgodovina